Expression and regulatory role of miRNA-222 in intervertebral disc degeneration (IDD). Issue 1 (1st January 2019) - Ge, Chen; Li, Changwei
Abstract: The aim of this study was to investigate the expression of miRNA-222 in intervertebral disc degeneration (IDD), and explore its regulatory mechanism. Totally 30 patients with IDD and 36 normal control subjects were included. Quantitative real-time polymerase chain reaction (PCR), Western blot analysis, and enzyme-linked immunosorbent assay (ELISA) were preformed to detect the mRNA and protein expression levels of MMP1, and the miRNA-222 expression levels, in the nucleus pulposus (NP) tissues and blood samples. Bioinformatics analysis was performed, and dual-luciferase reporter assay was conducted for confirmation. HNPC cells were cultured in vitro, and the effects of agomiRNA-222 transfection were analyzed. The results showed that MMP1 expression was significantly up-regulated in the NP tissues and blood samples of patients with IDD, and the miRNA-222 expression was significantly down-regulated in both specimens. Bioinformatics analysis showed that MMP1 was the direct target for miRNA-222, which was confirmed by the dual-luciferase reporter assay. Over-expression of miRNA-222 significantly decreased the expression levels of MMP1 in HNPC cells in vitro, and the expression levels of type II collagen were significantly up-regulated. These results suggest that MMP1 expression is up-regulated in the NP and blood of patients with IDD, which may be related to the down-regulation of miRNA-222. The miRNA-222 may regulate the expression of related proteins in intervertebral disc nucleus cells through MMP1, thus affecting the disease pathogenesis and development.